2021
DOI: 10.3390/ma14071658
|View full text |Cite
|
Sign up to set email alerts
|

Image Analysis of Surface Porosity Mortar Containing Processed Spent Bleaching Earth

Abstract: Image analysis techniques are gaining popularity in the studies of civil engineering materials. However, the current established image analysis methods often require advanced machinery and strict image acquisition procedures which may be challenging in actual construction practices. In this study, we develop a simplified image analysis technique that uses images with only a digital camera and does not have a strict image acquisition regime. Mortar with 10%, 20%, 30%, and 40% pozzolanic material as cement repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, the method used to design normal concrete mix cannot be used for designing a FC mix since it contains no coarse aggregate [ 37 ]. The foamed concrete mix design is commonly determined based on a trial and error approach [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The design of the experiment based on empirical or computational modelling [ 45 , 46 , 47 , 48 ] and statistical methods approaches have been implemented to analyze multifactor experiments and the model used in the prediction of compressive strength of foamed concrete with minimal mean square errors and standard deviation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the method used to design normal concrete mix cannot be used for designing a FC mix since it contains no coarse aggregate [ 37 ]. The foamed concrete mix design is commonly determined based on a trial and error approach [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The design of the experiment based on empirical or computational modelling [ 45 , 46 , 47 , 48 ] and statistical methods approaches have been implemented to analyze multifactor experiments and the model used in the prediction of compressive strength of foamed concrete with minimal mean square errors and standard deviation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous studies have been reported giving application examples of non-destructive testing techniques when detecting and locating anomalies in concrete [8]. Non-destructive testing is the testing of materials, for surface or internal flaws or metallurgical conditions, without interfering in any way with the integrity of the material or its suitability for service [9].…”
mentioning
confidence: 99%